(untitled) (Journal of Bangladesh Academy of Sciences, 2024)
Our study focuses on the butterfly checklist of the Adampur forest beat, located in the Rajkandi Reserve Forest of Moulvibazar, Bangladesh. The study was conducted between December 2014 and January 2018 and aimed to document butterfly species in the area. A total of 266 butterfly species belong to 149 genera and 6 families (Papilionidae, Pieridae, Nymphalidae, Lycaenidae, Hesperiidae, and Riodinidae) were recorded. The Lycaenidae family exhibited the highest species richness, comprising 33.08% (n = 88) of the recorded species, while the Riodinidae family was the least prevalent, representing 0.38% (n = 1) of the species. In this study, the butterfly species recorded revealed varying conservation status according to the International Union for Conservation of Nature Bangladesh assessment, with 26.69% listed as Endangered, 30.08% Least Concern, 23.68% Vulnerable, 1.50% Data Deficient, and 18.05% Not Evaluated. These findings offer crucial insights for future butterfly research and conservation in the Adampur forest beat. J. Bangladesh Acad. Sci. 48(1); 85-97: June 2024